2009
DOI: 10.1111/j.1463-1326.2009.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycaemic control and weight change in patients initiated with human or analog insulin in an US ambulatory care setting

Abstract: HbA1C outcomes in the ambulatory care setting were generally not different between insulin classes. The likelihood of weight gain was less with insulin detemir than with insulin glargine. Thus, real-world weight outcomes for basal analog insulin may differ by specific product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…In contrast, a study of 306 patients enrolled in a large United States (US) managed care organization found that glycemic control after 180 days was similar for insulin glargine and insulin detemir [9]. In addition, McAdam-Marx et al reported that patients with T2DM initiating insulin detemir were 30% less likely to gain 0.9 kg or more in body weight, with no significant difference in HbA 1c values, compared with insulin glargine [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study of 306 patients enrolled in a large United States (US) managed care organization found that glycemic control after 180 days was similar for insulin glargine and insulin detemir [9]. In addition, McAdam-Marx et al reported that patients with T2DM initiating insulin detemir were 30% less likely to gain 0.9 kg or more in body weight, with no significant difference in HbA 1c values, compared with insulin glargine [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The main message of this study is that the patient’s glucose profile predicts risk of weight gain, which is a known problem in starting insulin treatment in type 2 diabetes patients [17, 18]. This profile can be easily calculated from the fasting glucose/HbA1c ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with insulin detemir has been shown to result in less weight gain compared with insulin glargine use in both a head-to-head trial and a retrospective analysis of real-world data. 23 Insulin analog therapy is amenable to patient-driven dose adjustment, which can be advantageous for younger patients with busy lives as well as those with limited mobility and those who have difficulty obtaining transportation to their doctor. The use of a self-titration algorithm for adjusting basal insulin dosing versus standard-of-care, physician-guided dose adjustment was evaluated in the PREDICTIVE 303 (Predictable Results and Experience in Diabetes Through Intensification and Control to Target: an International Variability Evaluation) trial.…”
Section: Individualizing Glycemic Targetsmentioning
confidence: 99%